Application of microRNA gene resources in the improvement of agronomic traits in rice. Issue 3 (13th January 2015) - Zheng, Ling‐Ling; Qu, Liang‐Hu
Summary microRNAs (miRNAs) are important nonprotein‐coding genes that are involved in almost all biological processes, including cell differentiation and fate determination, developmental regulation, and immune responses. Investigations have shown that some miRNAs can highly affect plant agricultural traits, including virus resistance, nematode resistance, drought and salinity tolerance, heavy metal detoxification, biomass yield, grain yield, fruit development and flower development. Therefore, these miRNAs are considered a newly identified gene resource for the genetic improvement of crops. In this review, we will summarize the recent findings of the rice miRNA‐directed regulatory network, which controls agronomic traits such as yield, quality and stress tolerance, and explore the outlook for the uses of these miRNA‐associated traits in rice biotechnology.